Why is adoption of micro-irrigation slow in India? a review. Issue 1 (2nd January 2023) - Nair, Jyoti; Thomas, Bejoy K.
ABSTRACT: Adoption of micro-irrigation has been slow among farmers in India in spite of concerted efforts. Based on a systematic literature review, this article makes two observations. First, subsidies alone will not lead to greater adoption since decisions on adoption are shaped by household, farm level and institutional factors. Secondly, mere adoption of micro-irrigation will not result in water conservation because farmers are seen to expand the area under irrigation or shift to water-intensive crops. The article argues for better recognition of the diverse contextual factors and interests of farmers in formulating effective mechanisms to ensure adoption and use of micro-irrigation.